Analysis of the structure and conductance of Mg2+ acceptor-doped CaBi2Nb2-xMgxO9-3x/2 piezoceramics. Issue 10 (15th May 2022) - Wang, Hepeng; Jiang, Xiangping; Chen, Chao; Huang, Xiaokun; Nie, Xin; Jie, Shaotian; Yu, Xing
Abstract: In this work, Mg 2+ -doped CaBi2 Nb2 O9 (CBN- x Mg) lead-free piezoceramics were prepared by a common solid-state method to investigate the effects of Mg 2+ doping content on crystal structure, electrical resistivity, and dielectric and ferroelectric properties. XRD and Raman spectroscopy show that the Mg atoms enter the B -site to form a solid solution of the pure CBN phase. In addition, the XRD refinement results show that Mg 2+ doping increases the distortion of the NbO6 octahedron and simultaneously enhances the total contribution of the spontaneous polarization of each position along the a -axis, and that the P s increases from -28.678 μC/cm 2 for x = 0 to -31.768 μC/cm 2 for x = 0.02. However, when x > 0.02, the polarization decreases due to the oxygen vacancy pinning effect. According to SEM analysis, Mg 2+ doping strengthened the growth rate of CBN ceramic grains on the a - b plane, resulting in a more obvious plate-like structure. The reduced anti-site defects of the CBN ceramic samples strengthened the structure of (Bi2 O2 ) 2+ and improved the resistivity of the samples. The internal dipole moment was also strengthened, resulting in a significant increase in the dielectric constant and a decrease in the dielectric loss. In general, Mg 2+ doping significantly improved the comprehensive properties of CBN ceramics, with improved values including a d 33 of 11.1 pC/N, P r of 7.22 μC/cm 2, tan δ (600 °C) of 3.0%, and ρ dc (600 °C) of 10 8 Ωcm.